The Process of Making Schist Axes of Paja Ul Deˀŋ – “The People of Big Water” - Alexander Akulov (EXARC, 2021)
Paja Ul Deˀŋ [padʒaul’deˀŋ] “The People of Big Water” is a conventional and compact name given to Neolithic inhabitants of the territories of Saint Petersburg and the Leningrad region in their hypothetical reconstructed language (it is possible to state that these people spoke a language that was very close to Yeniseian languages). Paja Ul Deˀŋ made axes/adzes mainly of schist, a process that takes approximately a day of continuous work. If a stone is of oval shape and is relatively soft, an axe can be made in two or three hours. However, the harder the stone the stronger the axe. A heavier axe made of a harder stone with a wedge profile is more convenient for cutting a tree than a lighter axe with parallel sides made of relatively soft stone.